Recent advances and future directions in mantle cell lymphoma research: report of the 2018 mantle cell lymphoma consortium workshop. Issue 8 (3rd July 2019) - Kahl, Brad S.; Dreyling, Martin; Gordon, Leo I.; Martin, Peter; Quintanilla-Martinez, Leticia; Sotomayor, Eduardo M.
Abstract: Mantle cell lymphoma (MCL) is an aggressive B-cell non-Hodgkin lymphoma characterized by the t(11;14) chromosomal translocation. This translocation most often results in overexpression of cyclin D1. MCL is clinically heterogeneous, outcomes are generally poor, and no standard treatment has been established. The recent approvals of ibrutinib and acalabrutinib have provided an additional therapeutic option; however, resistance has emerged as a significant issue and presents the need for more detailed studies of resistance mechanisms. Recent clinical trials have provided new perspectives on the relative efficacy and safety of various approaches for both transplant-eligible and transplant-ineligible patients. Multiple novel strategies are being evaluated in the treatment of MCL, including both targeted agents and cellular immunotherapies. At the Lymphoma Research Foundation's 13th MCL Workshop, researchers gathered to discuss research findings, clinical trial results, and future directions related to MCL, its biology, and its treatment. This report, which includes a summary of each presentation, aims to review recent findings in MCL research and highlight potential areas for future study.